2022
DOI: 10.1177/19476035221118419
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma in the Repair of Articular Cartilage Injury: A Narrative Review

Abstract: Objective This paper reviews the research of platelet-rich plasma (PRP) in articular cartilage injury repair, to assess the mechanism, utilization, and efficacy of PRP in the treatment of articular cartilage injury, hoping to provide a theoretical basis for the clinical application of PRP in the future. Materials and Methods A comprehensive database search on PRP applications in cartilage repair was performed. Among them, the retrieval time range of PRP in clinical trials of repairing knee cartilage injury was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 124 publications
0
7
0
1
Order By: Relevance
“…The regeneration of articular cartilage has been an important topic in both academic and clinical fields for a long time [54][55][56][57][58][59][60][61][62]. Although efforts had been made by plenty of researchers, very few materials could turn into effective biomedical products.…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of articular cartilage has been an important topic in both academic and clinical fields for a long time [54][55][56][57][58][59][60][61][62]. Although efforts had been made by plenty of researchers, very few materials could turn into effective biomedical products.…”
Section: Discussionmentioning
confidence: 99%
“…A balance between catabolic and anabolic forces, and consequently over the rates of cellular development and destruction, is necessary for tissue health. Regeneration is observed to be aided by catabolic factors, primarily in the case of articular cartilage [61]. Due to the drawbacks of the gold-standard therapeutic approaches for problems of cartilage tissue, PRP and related derivatives have gained popularity in recent years [62].…”
Section: Cartilage and Fibrocartilagementioning
confidence: 99%
“…Due to the drawbacks of the gold-standard therapeutic approaches for problems of cartilage tissue, PRP and related derivatives have gained popularity in recent years [62]. The main part of the treatment involves injecting PRP into the intraarticular area, which protects the chondrocytes, thereby altering the levels of catabolic factors [61,63]. Osteoarthritis (OA), which affects millions of people worldwide and is treated with surgical procedures that require lengthy recovery times, is a significant concern in the field of cartilage disorders.…”
Section: Cartilage and Fibrocartilagementioning
confidence: 99%
“…For those with OA, current strategies to optimize the delivery vehicle have included the use of existing biological fluids such as PRP, or synthesized biological material such as HA. PRP has been cited to reduce the occurrence of inflammation, improve angiogenesis, and promote the proliferation and differentiation of chondrocytes by secreting cytokines, chemokines, and growth factors, as well as exosomes with similar effects, so as to promote the healing of bone and cartilage injuries ( Liang et al, 2022 ). In clinical studies, patients with knee OA treated with PRP showed improvement in physical function and pain, suggesting that intra-articular injection of PRP may be a potential therapeutic strategy for relieving knee pain ( Liang et al, 2022 ; Riewruja et al, 2022 ).…”
Section: Future Directionsmentioning
confidence: 99%